Gamification versus traditional teaching: Impacts on mathematics learning outcomes and engagement - Edy Sucipto; Ibrahim Bafadal; Siti Mas’ula (Universitas Papua, 2026)
This quasi-experimental study examined the effectiveness of low-tech gamified mathematics instruction compared with traditional teaching in an Indonesian elementary school. Intact classes at SD Negeri 001 Tana Tidung (Sesayap, North Kalimantan) were assigned to gamification (n=47) or traditional (n=46). Both groups completed a 25-item pretest and posttest across 4–6 sessions. The primary outcome was posttest achievement analyzed with ANCOVA (covariate: pretest); secondary indicators were N-Gain, Hedges’ g, mastery (≥70), on-task engagement, and treatment fidelity. Results showed a significant group effect, F(1,89)=11.0, p=0.0012, partial η²=0.11. Adjusted means favored gamification (79.2; 95% CI [77.0, 81.4]) over traditional (72.7; [70.4, 75.0]), Δ=6.5; g≈0.70. N-Gain was 0.53 (gamification) vs 0.37 (traditional). Mastery reached 83.0% vs 63.0% (OR=2.60, 95% CI [1.20, 5.60]). Engagement was higher under gamification (78.6% vs 68.1%) and positively predicted posttest (β=0.28, p=0.004). Fidelity averaged 88% (κ=0.79). Findings indicate that progress- and process-oriented gamification with immediate feedback improves learning outcomes and classroom engagement, offering a feasible, scalable option for resource-limited settings.